マウスB16-BL6細胞における酸性細胞外pH誘導性MMP-9発現誘導経路に対するPAK6/7の役割 - 川嶋, 雅之; 加藤, 靖正; 御代田, 駿; 小嶋, 忠之; 前田, 豊信; 高田, 訓 (日本口腔外科学会雑誌, 2024)
It is well known that extracellular pH (pHe) tumor tissue is acidic, and sometimes induces matrix metalloproteinase-9 (MMP-9) expression, invasion and metastasis. The small G protein RhoA plays a role in the intracellular signaling pathway for acidic pHe. In this study, PAK6 and PAK7, two of the p21 activated kinases (PAKs) that are known to act downstream of small G proteins, were investigated and their role in acidic pHe signaling inducing MMP-9 expression was examined. PAK6 and PAK7 double knockout cell variants (PAK6/7 KO cells) of mouse B16-BL6 melanoma were prepared via the CRISPR / Cas9 method. MMP-9 activity and mRNA levels were analyzed by gelatin zymography and quantitative PCR, respectively. Enforced expression of PAK6/7 decreased the induction of MMP-9 in parental B16-BL6 cells. On the contrary, the acidic pHe-induced MMP-9 expression level in PAK6/7 KO cells was higher than in parental cells, while MMP-9 induction was absent in PAK6/7 KO cells at neutral pHe. When PAK6/7 KO cells were rescued by introduction of vectors expressing wild type PAK6/7 and its mutants including constitutively active and kinasedead forms, acidic pHe-induced MMP-9 expression was suppressed by the introduction of wild-type and constitutively active PAK6/7, but not by the kinase-dead forms. These results suggest that PAK6/7 play a role of negative feedback in acidic pHe signaling to induce MMP-9 expression.